2023
DOI: 10.1055/a-2010-4009
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Propylene Glycol Extract of Propolis on Central Nervous System and Liver in Pregnant and Neonatal Rats

Abstract: Background Propolis has become one of the most preferred supplements due to its beneficial biological properties. Organic (water and vegetable oils) and chemical (ethyl alcohol, propylene glycol, and glycerol) solvents are used for propolis extraction. However, the effects of these chemicals on health should be taken into account. Objectives In this study, the effects of propolis extracts on health were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Furthermore, it was observed that propylene glycol extracts of propolis exhibited higher toxicity levels compared to olive oil and water extracts. Consequently, olive oil and water extracts of propolis are regarded as safer alternatives for pregnant and infant rats in comparison to propylene glycol extract [28].…”
Section: Propolismentioning
confidence: 99%
“…Furthermore, it was observed that propylene glycol extracts of propolis exhibited higher toxicity levels compared to olive oil and water extracts. Consequently, olive oil and water extracts of propolis are regarded as safer alternatives for pregnant and infant rats in comparison to propylene glycol extract [28].…”
Section: Propolismentioning
confidence: 99%